Belle de jour [videorecording (DVD)] - Buñuel, Luis, 1900-1983; Buñuel, Luis, 1900-1983; Deneuve, Catherine, 1943-; Sorel, Jean, 1934-; Piccoli, Michel, 1925-2020-; Page, Geneviève; Kessel, Joseph, 1898-1979 (Criterion collection, 2012)
The porcelain perfection of Catherine Deneuve hides a cracked interior in the actress's most iconic role: Severine, a chilly Paris housewife by night, a bordello prostitute by day.